IMPLEMENTATION OF THE PARAS VILLAGE FUND POLICY, CEPOGO DISTRICT, BOYOLALI REGENCY IN HANDLING CORONA VIRUS DISEASE (COVID 19) - Razali Hadipuro; Supardal Supardal (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Implementation of the Paras Village Fund Policy, Cepogo District, Boyolali Regency in Handling Corona Virus Disease (Covid 19), In Handling Covid-19. Thesis. Government Science Masters Program. STPMD